A “Timed” Kiss Is Essential for Reproduction: Lessons from Mammalian Studies - Putteeraj, Manish; Soga, Tomoko; Ubuka, Takayoshi; Parhar, Ishwar S. (Frontiers in Endocrinology, 2016)
Reproduction is associated with the circadian system, primarily as a result of the connectivity between the biological clock in the suprachiasmatic nucleus (SCN) and reproduction-regulating brain regions, such as preoptic area (POA), anteroventral periventricular nucleus (AVPV) and arcuate nucleus (ARC). Networking of the central pacemaker to these hypothalamic brain regions is partly represented by close fiber appositions to specialised neurons, such as kisspeptin and gonadotropin-releasing hormone (GnRH) neurons; accounting for rhythmic release of gonadotropins and sex steroids. Numerous studies have attempted to dissect the neurochemical properties of GnRH neurons, which possess intrinsic oscillatory features through the presence of clock genes to regulate the pulsatile and circadian secretion. However, less attention has been given to kisspeptin, the upstream regulator of GnRH and a potent mediator of reproductive functions including puberty. Kisspeptin exerts its stimulatory effects on GnRH secretion via its cognate Kiss-1R receptor that is co-expressed on GnRH neurons. Emerging studies have found that kisspeptin neurons oscillate on a circadian basis and that these neurons also express clock genes that are thought to regulate its rhythmic activities. Based on the fiber networks between the SCN and reproductive nuclei such as the POA, AVPV, ARC, it is suggested that interactions among the central biological clock and reproductive neurons ensure optimal reproductive functionality. Within this neuronal circuitry, kisspeptin neuronal system is likely to ‘time’ reproduction in a long term during development and ageing, in a medium term to regulate circadian or estrus cycle, and in a short term to regulate pulsatile GnRH secretion.